STRATEGI PENGUATAN GALANGAN KAPAL NASIONAL DALAM RANGKA MEMPERKUAT EFEKTIFITAS DAN EFISIENSI ARMADA PELAYARAN DOMESTIK - Bayu satrio (Fakultas Sains dan Teknologi Universitas Karimun, 2021)
The development of the national maritime industry as a solution for the Indonesian government's program to increase the capability in national shipping, both in the transportation of goods and passengers between islands. For initial data as a guideline for increasing the shipyard's ability to produce new shipbuilding including repair / docking, it is necessary to have an inventory of current shipyard conditions and operational capabilities in building and repairing ships according to the existing schedule. shipyards and production infrastructure in use today, a large investment is still needed, including the addition of professional and integrated human resources. As we all know, shipyard is a capital-intensive and labor-intensive industry, especially in Indonesia. From the Resume, evaluation of secondary data shows that the contribution of shipyard operations is more oriented to ship repair / repair (docking), because material needs are more localized. In addition, the risk of loss and working time can be minimized from the need for more locally loaded materials